PENGARUH SALES PROMOTION, CUSTOMER EXPERIENCE, DAN BRAND IMAGE TERHADAP REPURCHASE INTENTION - Sewakottama, Nyoman Gede Rastra; Prawitasari, Putu Putri; Tirtayani, I Gusti Ayu; Ariwangsa, I Gusti Ngurah Oka (Jurnal Bina Bangsa Ekonomika, 2025)
The purpose of this study is to reveal the influence  of sales promotion, customer experience, and brand image partially and simultaneously on repurchase intention. The sample of this study amounted to 100 Gen Z consumers who visited Starbucks branches in Ubud. Data analysis techniques include validity test, reliability test, classical assumption test, multiple regression analysis, determination coefficient test, F test, and t test. The results of the study show that sales promotion, customer experience, and brand image have a significant effect on repurchase intention, sales promotion has a positive and significant effect on repurchase intention,  customer experience has a positive and significant effect on repurchase intention, Brand image has a positive and significant effect on repurchase intention. This has a significant positive influence on repurchase interest. The magnitude of the influence of independent variables on repurchase interest was 59.5%. The suggestions that researchers can give are as follows: It is recommended that Starbucks Ubud stores proactively provide information whenever there is a promotion of a product package at a lower price to consumers, so that more consumers need to buy, assess your employees' communication skills, and provide training to your employees. Always provide products that suit the consumer's lifestyle, promote well, provide a good experience to consumers, and build a good image in the eyes of consumers